2006
DOI: 10.1079/ivp2006822
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and carbohydrate status of easy-and difficult-to-acclimatize sea oats (Uniola paniculata L.) genotypes during In vitro culture and Ex vitro acclimatization

Abstract: SummaryThe photosynthetic and carbohydrate status of an easy-to-acclimatize (EK 16-3) and a difficult-to-acclimatize (EK 11-1) genotype of Uniola paniculata L. (sea oats), a native dune species of the southeastern US, were evaluated during in vitro culture and ex vitro acclimatization. Net photosynthetic rate was eight times greater for EK 16-3 than EK 11-1 plantlets after ex vitro transfer. In vitro-produced leaves were morphologically similar to ex vitro-produced leaves and exhibited similar photosynthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
1
13
1
2
Order By: Relevance
“…With sea oats genotypes such as EK 16-3, we observed that the development of elongated leaves with fully expanded blades produced in vitro was critical to shoot establishment ex vitro. We have observed this response in previous studies (Valero-Aracama et al, 2006). EK 16-3 plantlets cultured in vitro under control conditions had greater photosynthetic capacity at the time of ex vitro transfer than EK 11-1 control plantlets as indicated by their initial P nl ex vitro.…”
Section: Discussionsupporting
confidence: 57%
“…With sea oats genotypes such as EK 16-3, we observed that the development of elongated leaves with fully expanded blades produced in vitro was critical to shoot establishment ex vitro. We have observed this response in previous studies (Valero-Aracama et al, 2006). EK 16-3 plantlets cultured in vitro under control conditions had greater photosynthetic capacity at the time of ex vitro transfer than EK 11-1 control plantlets as indicated by their initial P nl ex vitro.…”
Section: Discussionsupporting
confidence: 57%
“…The identification of genotypes differing in responses is particularly useful. For example, easy-and difficultto-acclimatise genotypes of Uniola paniculata L. have been used to study physiological factors correlated with acclimatisation (Valero- Aracama et al 2006;Aracama et al 2008). Continued physiological, developmental and morphological research directed at the responses needed for in vitro propagation and preservation can only improve the usefulness of these methods.…”
Section: Scientific/technical Challengesmentioning
confidence: 99%
“…Only during the first day of in vitro introduction, a decrease in Fv/Fm was observed in basal scions (P = 0.01; Figure 3). Such small Fv/Fm reduction could be attributable to the physiological stress imposed by the excision from ortet, and then the in vitro introduction [39] [40]. Despite this, we find a fast scions Fv/Fm recovery, due to the in vitro culture conditions, which also exert the surpass of Fv/Fm values measured in the ortet Figure 2.…”
Section: Resultsmentioning
confidence: 63%